(untitled) (Vietnam Journal of Community Medicine, 2024)
Through research on anesthesia and 24-hour perioperative resuscitation for 75 patients undergoing adrenal adenoma surgery, we drew the following conclusions: 1. Pheochromocytoma patients requyred 7-10 days of treatment with alpha-blockers or combined beta-blockers to stabilize blood pressure and heart rate before surgery. High blood pressure and hypokalemia must be managed before surgery. During adrenal tumor surgery, invasive arterial blood pressure monitoring is essential, along with additional central venous lines for recurrent or enlarged adenomas. Urinary and gastric catheters should be placed, and medications for blood pressure and heart rhythm control prepared. Hydrocortisone supplementation during and after surgery to prevent adrenal insufficiency. Anesthesiologists must coordinate with surgeons to maintain stable blood pressure during tumor manipulation (when the surgeon pulls or dissects the tumor causing increased blood pressure; the surgeon clamps the main adrenal vein causing hypotension). 2. Endotracheal anesthesia provided effective anesthesia for adrenal gland tumor surgeries, with an average duration of 72.2 ± 16.3 minutes. Conn’s syndrome and pheochromocytoma patients requyre more anesthetics and muscle relaxants than those with non-secreting tumors or Cushing’s syndrome. Hemodynamic disturbances occurred in all patients with Conn’s syndrome, Cushing’s syndrome, and pheochromocytoma, but only in 2 of 13 (11.5%) with non-secreting tumors. Medication is administered to stabilize heart rate and blood pressure in these cases. No significant difference in average blood pressure and heart rate was observed between pheochromocytoma and adrenocortical tumor patients 30 minutes before and 3 hours after surgery, but significant differences were noted during surgery (p < 0.05). All patients had good respiratory status before and after surgery, and both patients and surgeons were satisfied with the anesthesia 48 hours post-surgery